Analisis Keterampilan Berpikir Kritis Dalam Menyelesaikan Soal Termodinamika Melalui Model SQ3R (Survey, Question,Read, Recite, Review) - Andi Rezki Awalia Ramadhani; suarti, suarti (Al-Khazini, 2022)
Thisstudy aims to describe students' critical thinking skills in solving thermodynamic problems after applying the SQ3R learning model (survey, question, read, recite, review) combined with reading literacy. The research method used in this study is a descriptive method with a quantitative approach. The research subjects were 31 students of class XI IPA 3 of SMAN 1 Maros. The data collection technique used is a multiple choice objective test of 15 numbers consisting of indicators of critical thinking ability: giving simple explanations, building basic skills, concluding, making further explanations, making strategies and concept techniques that include aspects of the ability to analyze and evaluate. Based on data analysis, it was found that the average critical thinking skills of students in thermodynamics learning were 79.80 in the high category, with details as follows: (1) The percentage of students who had a very high level of critical thinking skills was 19. ,35%, high category 80.65%, medium category 0%, low category 0% very low category 0%; (2) The percentage of students' ability to answer questions on indicators of ability to provide simple explanations is 95%, basic skills are 100%, conclude 72%, make further explanations 73% and the ability to make strategies and concepts 45%.